Evaluación del rol de la iluminancia, el ph y la cantidad de nutrientes en el crecimiento de la microalga Scenedesmus sp. En condiciones de laboratorio - Pástor Guerrero, Vidal Patricio (2013)
This research focuses on Scenedesmus sp. which is a microalgae of Scenedesmaceae family. The growth parameters are specific for each species of microalgae and facilitate subsequent use in industrial or laboratory fields. The objective of the study was to evaluate the influence of illuminance, pH and the amount of nutrients in the growth of the microalgae Scenedesmus sp. The strain was obtained from the Microbiology Laboratory of Catholic University of Ecuador. For the research a prototype of incubator was manufactured adapted to the conditions of cultivation. Each parameter study was replicated 8 times and maintained for 5 days as the experimental model. To perform the growth curves and the statistical treatment were measured daily for cell count per container. The statistical analysis displayed a better growth in pH 8, illuminance of 32W, and medium concentrations showed no significant difference between groups.